Mulch and herbicide impact on weed management, nodulation and quality of soybean [Glycine max L. Merrill] - Datta, Debarati; Saxena, S.C.; Ghosh, Sourav (Annals of Agricultural Research, 2018)
A field experiment was conducted during kharif 2015 at N. E. Borlaug Crop Research Centre of Govind Ballabh Pant University of Agriculture and Technology, Pantnagar (Uttarakhand) to assess the impact of three herbicides viz. Pendimethalin, Imazethapyr and Sulfentrazone along with wheat straw mulch on weed dynamics, nodulation, yield and quality of soybean. Pendimethalin (PE) fb imazethapyr (PoE) + mulching @5t/ha (25 DAS) recorded significantly lower weed density and highest weed control efficiency as compared to other treatments. However, it was at par with mulching after 1st weeding at 25 DAS and mulching fb sulfentrazone (PoE). Pendimethalin fb imazethapyr + mulching (25DAS) resulted in considerably higher seed and biological yield (2.6 and 7.9 t/ha, respectively) and was comparable with weed free check (2.7 and 8.2 t/ha, respectively). Nodule number and dry weight was higher in plots applied with mulch. No significant variation in oil and protein content of soybean seeds was obtained